2018
DOI: 10.1002/btpr.2736
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of the −1 Amino Acid on Yeast Production of Protein‐Intein Fusions

Abstract: Expressing antibodies as fusions to the non‐self‐cleaving Mxe GyrA intein allows for site‐specific chemical functionalization via expressed protein ligation. It is highly desirable to maximize the yield of functionalizable protein; and previously an evolved intein, 202‐08, was identified that could increase protein fusion production in yeast. Given that the −1 amino acid residue upstream of inteins can affect cleavage efficiency, we examined the effects of amino acid variability at this position on 202‐08 inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…Additionally, SDS‐PAGE showed that the ~35% of unbound biotin‐labeled mRuby3 was generated by an incomplete IPL reaction. The IPL reaction and Intein cleavage have been previously shown to be strongly dependent on the C‐terminal amino acid of the protein of interest 32,42 . Moreover, the efficiency of cleavage and IPL were shown to be able to increase with longer (up to 40 hr) incubation times.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…Additionally, SDS‐PAGE showed that the ~35% of unbound biotin‐labeled mRuby3 was generated by an incomplete IPL reaction. The IPL reaction and Intein cleavage have been previously shown to be strongly dependent on the C‐terminal amino acid of the protein of interest 32,42 . Moreover, the efficiency of cleavage and IPL were shown to be able to increase with longer (up to 40 hr) incubation times.…”
Section: Resultsmentioning
confidence: 93%
“…The IPL reaction and Intein cleavage have been previously shown to be strongly dependent on the C-terminal amino acid of the protein of interest. 32,42 Moreover, the efficiency of cleavage and IPL were shown to be able to increase with longer (up to 40 hr) incubation times. Nevertheless, we intentionally restricted the IPL reaction time to only 12 h to capture this limitation.…”
Section: Purification Of Ipl-ready Mruby3 Using the Tsgit Systemmentioning
confidence: 97%